Restorable piezochromism phenomenon in an AIE molecular crystal: combined synchronous Raman scattering. (5th December 2016) - Liu, Liqun; Wang, Kai; Deng, Jian; Zhang, Zhe; Wang, Yan; Ma, Yuguang
Abstract : Many AIE active molecules have been designed and synthesized, and have been found to possess many interesting characteristics. In recent years, research into AIE crystals has increased, and it has been clearly shown that the piezochromic effect of AIE crystals depends on their structure. While most of the related research has given qualitative results, to quantitatively reveal molecular conditions under different pressure conditions, crystals of an AIE material (2 Z, 2′ Z )-3, 3′-(1, 4-phenylene)bis(2-(naphthalen-2-yl)acrylonitrile) were investigated by synchronous Raman scattering and fluorescence spectroscopies. The molecular structure of the crystal changed during the process of pressurizing and then depressurizing under hydrostatic pressure, and a 142 nm red-shift value was observed in the emission spectrum of the PBNA crystal. The crystal was transformed into a new phase when the pressure was above 1.03 GPa and returned to the original phase when the pressure was decreased. The unique restorable phase transformation process of the crystal of this AIE active material could be used for erasable optical information storage and stress sensing devices.